Long‐Term Outcomes Following Left Atrial Appendage Occlusion in Medicare Beneficiaries: Outcomes From the National Cardiovascular Data Registry - Angela Y. Higgins; Sarah Zimmerman; Yongfei Wang; Daniel J. Friedman; Kamil F. Faridi; Matthew J. Price; Vivek Y. Reddy; David R. Holmes; Jeptha P. Curtis; James V. Freeman (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Percutaneous left atrial appendage occlusion (LAAO) is an alternative to long‐term anticoagulation for preventing ischemic stroke in patients with atrial fibrillation. There are limited long‐term outcomes data for “real‐world” patients undergoing LAAO. Methods We performed a retrospective cohort study using the National Cardiovascular Data Registry LAAO registry from January 1, 2016, through December 31, 2019. We linked LAAO data to inpatient Medicare fee‐for‐service claims data using probabilistic matching to establish a cohort of patients 65 years and older undergoing LAAO with a WATCHMAN device. The primary outcomes were any stroke and all‐cause mortality. Results A total of 34 975 patients with a mean±SD CHA2DS2‐VASc (congestive heart failure, hypertension, age ≥75 years, diabetes, previous stroke or transient ischemic attack, vascular disease, age 65 to 74 years, and sex category) score of 4.7±1.4 were included. The median follow‐up was 2.8 years (interquartile range, 2.2–3.7 years). The cumulative incidence of any stroke was 1.57 per 100 person‐years (95% CI, 1.45–1.70), with a 1‐year and 5‐year any stroke estimate of 1.70% (95% CI, 1.57–1.84%) and 5.70% (95% CI, 5.37–6.05%), respectively. The cumulative incidence of ischemic stroke was 1.36 per 100 person‐years (95% CI, 1.25–1.48), with a 1‐year and 5‐year ischemic stroke estimate of 1.42% (95% CI, 1.30–1.54%) and 5.03% (95% CI, 4.71–5.36%), respectively. The cumulative incidence of death was 10.82 per 100 person‐years (95% CI, 10.49–11.13), with a 5‐year mortality estimate of 44.34% (95% CI, 43.35–45.23%). Conclusions Long‐term stroke rates in a large nationally representative cohort of Medicare patients following LAAO were low and durably consistent during long‐term follow‐up despite a high thromboembolic risk. High mortality rates in this elderly population underscore the importance of incorporating patient values and preferences when considering LAAO.